Cost analysis of biodiesel from kernel oil of tea seed. Issue 5 (4th May 2017) - Demirbas, Ayhan; Kinsara, Rami A.
ABSTRACT: Currently, biodiesel is mainly produced from conventionally grown edible oils such as soybean, rapeseed, sunflower, and palm. To obtain biodiesel from edible oils is currently not economically feasible to substitute petroleum diesel. Biodiesel was obtained from kernel oil of tea seed ( Camellia sinensis L. Kuntze ). The predominant fatty acid was oleic acid (62.5% wt) in the tea kernel oil, followed by linoleic acid (18.1% wt). The seed kernel oil was transesterified to methyl esters using KOH catalytic methanol. The tea kernel oil has lower pour point and lower viscosity compared with common vegetable oils. Lower-cost raw materials are needed since biodiesel from food-grade oils is not economically competitive with petroleum-based diesel fuel. Biodiesel production costs can vary widely by feedstock, conversion process, scale of production, and geographic region. The cost of feedstock is a major economic factor in the viability of biodiesel production. Feedstock costs typically account for 60–80% of the total costs of biodiesel production. The crude tea kernel oil is one of the cheapest raw materials for biodiesel production.